Do the total mercury concentrations detected in fish from Czech ponds represent a risk for consumers? - Pavla, Sehonova; Danka, Harustiakova; Premysl, Mikula; Denisa, Medkova; Kristyna, Malacova; Zdenka, Svobodova (Scientific reports, 2022)
Mercury is one of the important pollutants of the environment. Therefore, it's necessary to monitor quantity of mercury especially in aquatic ecosystems. The main goal of the presented study was to compare the content of total mercury in tissues of fish coming from the Czech Republic, an important carp exporter, with focus on comparison of mercury content between 3 different ponds, its comparison between different fish species and between different tissues of the same species, and estimation whether the mercury content in tissues meets the limit given in the Commission Regulation (EC) No. 1881/2006 or not. Total mercury concentration was measured in 90 fish specimen sampled from three ponds (Velky Kocelovicky, Mysliv and Zehunsky) in autumn 2018. The values of total mercury in fish tissues was measured by atomic absorption spectrometry. The content of total mercury in the tissues decreased as follows: muscle > liver > gonads > scales. The highest average content of total mercury in muscle was 0.1517 ± 0.0176 mg/kg coming from pike caught in Velky Kocelovicky pond. In contrast, the lowest average content of total mercury in muscle 0.0036 ± 0.0003 mg/kg was found in carp tissue coming from the locality of Zehunsky pond. We confirmed that the predatory fish are more exposed to mercury than non-predatory fish. None of the monitored localities exceeded the set regulatory limit. Thus, our study shows that fish coming from these ponds are safe in terms of total mercury content.
Keywords: monitorování životního prostředí; Ponds; Česká republika; Environmental Monitoring; kapři; rybníky; rtuť; Czech Republic; chemické látky znečišťující vodu; kontaminace potravin; Mercury; Carps; Water Pollutants, Chemical; zvířata; Humans; Food Contamination; Fishes; ryby; lidé; Animals